11.3+-7.2f=-3.82

Simple and best practice solution for 11.3+-7.2f=-3.82 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11.3+-7.2f=-3.82 equation:


Simplifying
11.3 + -7.2f = -3.82

Solving
11.3 + -7.2f = -3.82

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-11.3' to each side of the equation.
11.3 + -11.3 + -7.2f = -3.82 + -11.3

Combine like terms: 11.3 + -11.3 = 0.0
0.0 + -7.2f = -3.82 + -11.3
-7.2f = -3.82 + -11.3

Combine like terms: -3.82 + -11.3 = -15.12
-7.2f = -15.12

Divide each side by '-7.2'.
f = 2.1

Simplifying
f = 2.1

See similar equations:

| 48t+265=553 | | 5x+3=14x-42 | | F(x)=x^2-3x-4/x^2-25 | | 2x+2x+x+9+x+9=84 | | =3-4n+9 | | w-0.06w=26.32 | | [5-2x]+3=8 | | 3-3x=27 | | 6z+3z=72 | | 10r+100s+50r=0 | | (-16/8)-1/8 | | 4*8+9(3a+5)+8(2a+1)=0 | | -16/8-1/8 | | p^2-14=0 | | (3x+4)-2(x-4)=4(x+6)+5x | | 139*14= | | 5w+3=12+2w | | 16x^2-6x-5=0 | | .91Y+1=y-.8 | | 12(c+3d+4f)+2(2c+d+6f)=0 | | 7=3-5x+4 | | 8(r+15)+7(2r+10)=0 | | x+5x+8(x+2)=0 | | 5d=-1-24 | | 5(x+2y)+6x=0 | | n+(n+1)=269 | | 5-5[2-(3y-3)]= | | -24=-6w+3(w-5) | | (5x+2)m=131 | | (5x+3)m=131 | | 5(x+1)=2+5x | | 4(x)m=131 |

Equations solver categories